2012
DOI: 10.1074/jbc.m112.342725
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequence of Covalent Reaction of Phosphoenolpyruvate with UDP-N-acetylglucosamine 1-Carboxyvinyltransferase (MurA)

Abstract: Background:MurA is critical for the biosynthesis of the bacterial cell wall. Results: The covalent MurA-phosphoenolpyruvate adduct was captured in different reaction states. Conclusion: The covalent adduct primes phosphoenolpyruvate for catalysis and enables feedback inhibition by UDP-N-acetylmuramic acid, the product of MurB. Significance: Cellular MurA exists in a previously unrecognized and tightly locked complex, which presumably accounts for the failure of drug discovery efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 31 publications
5
69
0
1
Order By: Relevance
“…Recent studies have shown that MurA forms dormant complexes with UDP-N-acetylmuramic acid (UDP-MurNAc), which is the product of MurB, the second enzyme partici-pating in peptidoglycan synthesis. This supports the idea that Cys115 provides tight product regulation and protection, which are absent from species containing aspartic acid in this position (30).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Recent studies have shown that MurA forms dormant complexes with UDP-N-acetylmuramic acid (UDP-MurNAc), which is the product of MurB, the second enzyme partici-pating in peptidoglycan synthesis. This supports the idea that Cys115 provides tight product regulation and protection, which are absent from species containing aspartic acid in this position (30).…”
supporting
confidence: 81%
“…A previous study reported that the product of the MurB enzyme UDP-MurNAc of E. cloacae binds tightly to MurA, creating a dormant complex. Therefore, UDP-MurNAc could act as a negative feedback regulator of MurA when it is present in excess (30). Because the murB sequences of Hungary 19A and D39 differ, we tested whether murB switch mutants of strains D39 (GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work (Zhu et al 2012) indicates that, in the cell, the activity of MurA is subject to regulation by the binding of UDP-NAc-muramic acid (UDP-MurNAc), the product of the MurB enzyme, to MurA. In the presence of bound UDP-MurNAc, PEP covalently attaches to C115, leading to the formation of a "locked" dormant tertiary complex (MurA:PEP-UDPMurNAc), which is the predominant form of cellular MurA.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The assay developed by Zhu and colleagues (2012) [49] revealed that the cysteine and aspartate side chains adopt similar positions and conformations in the PEP binding site through a general acid-–base mechanism with rapid and reversible binding of PEP. The results of this study imply that the cysteine or aspartate residue at position 115 of E. coli (residue 117 in M. tuberculosis ) performs the role of a general acid in the protonation of C-3 of PEP during the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Superposition of the calculated MurA protein of M. tuberculosis (blue) and H. influenzae (green – 3SWE) [49]. Catalytic residues are shown.…”
Section: Figurementioning
confidence: 99%